Study of Incidence and Severity of Coronary Artery Stenosis at Autopsy - Ina Patel; Kuldip Teraiya; Rahul A Mehta (Indian Journal of Forensic Medicine and Pathology, 2025)
Backgrounds: The occurrence of sudden cardiac death (SCD) has been continuously rising globally. Identi𿿿cation of modi𿿿able risk factors may help reduce theincidence of sudden cardiac death. Aims: This study aimed to evaluate the incidence, associated risk factors, myocardial ischemic changes, and the speci𿿿c arterial involvement in individuals who died due to a cardiac event. Material and method: The study was conducted at the Department of Forensic Medicine, Shri M. P. Shah Govt. Medical College, Jamnagar, from January 2023 to December 2023. A total of 110 cases of sudden death were included in the study. The heart was examined in these cases for both gross and myocardial analysis. Results: Left anterior descending artery (27.27%) was the most commonsite of stenosis, followed by left main artery (13.63%). The main feature was softening (8.18%) of myocardium, followed by hyperemia (4.54%) and myocardial𿿿brosis (3.63%) in the cases showing gross changes of ischemia. Conclusion: Sudden death caused by acute myocardial infarction mainly affects middle-aged individuals, with an increasing trend in younger people. The most common artery affected by stenosis was the left anterior descending artery, with most cases showing grade-3 or grade-4 stenosis. The left lateral wall is the most common site of infarction. Hypertension, Diabetes, nicotine consumption and drinking habits are the major risk factors. Nicotine and drinking habits can accelerate the development of coronary artery stenosis.